Curahan Tenaga Kerja Petani pada Usahatani Padi Sawah di Desa Tumani Selatan Kecamatan Maesaan Kabupaten Minahasa Selatan (Farmer Labor Outpouring on Rice Field Business in Tumani Selatan Village, Maesaan Sub District South Minahasa Regency) - Natalia Hillary Pesik; Sherly G. Jocom; Jelly R. D. Lumingkewas (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to determine the outpouring of farmers' labor in lowland rice farming. The research was conducted in South Tumani Village, Maesaan Sub District, South Minahasa Regency. Data was collected using a survey method using primary and secondary data. The number of samples of paddy rice farmers was determined to be 20 people. Sampling using purposive sampling method, the sample is taken intentionally. Data analysis was done descriptively. The types of lowland rice farming activities under study include soil processing, seeding, planting, weeding, fertilizing, eradicating pests and diseases, harvesting, transporting and drying or drying. The research results showed that the average outpouring of farmer labor on 1 hectare rice farming is 103.42 HKSP/Ha, consisting of 89.47 HKSP/Ha and 13.95 HKSP/Ha. The largest workforce occurred in planting activities, namely 33.94 HKSP/Ha or 32.82%, followed by harvesting activities of 32.09 HKSP/Ha or 31.03% and land processing activities of 31.66 HKSP/Ha or 30, 61%.